Spontaneous expectoration of a Blalock-Taussig shunt a decade after operation - Shyam S Kothari; Madhan Kumar Murugan; Ujjwal Kumar Chowdhury (Wolters Kluwer Medknow Publications, 2015)
An eleven-year-old boy expectorated a foreign body in cough that was identified as the prosthetic graft used for a Blalock-Taussig shunt. The shunt procedure was done 10 years earlier, and a definitive repair for tetralogy of Fallot was done a year later. He had no other symptoms, and a computed tomography (CT) angiogram did not reveal any other significant anomaly. The reason for this extremely rare event is unclear.